1958
DOI: 10.1037/h0044688
|View full text |Cite
|
Sign up to set email alerts
|

Factor analysis of interview interaction behavior.

Abstract: Our research program has utilized the Chapple Interaction Chronograph for recording the speech and silence behavior of interviewers and interviewees. This paper describes a new electronic interaction Recorder which is more efficient than the earlier recording device. The paper also demonstrates that data collected by these two devices are almost identical. Twenty interviews were recorded simultaneously, on both instruments, and twelve different measures were compared by means of correlation, and through inspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1961
1961
1987
1987

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…The longer a person talks the more chances he has to pause, but assuming that time is equated in verbal samples, verbal quantity and pauses tend to be negatively correlated, sometimes at statistically significant levels ranging as high as -.68 (Goldman-Eisler, 1961), while verbal quantity and reaction time also tend to be negatively related, though significantly so in only one (Matarazzo, Saslow, & Hare, 1958) of five studies. The longer a person talks the slower his speech rate, though of four studies none reported a significant relationship (for example, Kelly & Steer, 1949).…”
mentioning
confidence: 97%
“…The longer a person talks the more chances he has to pause, but assuming that time is equated in verbal samples, verbal quantity and pauses tend to be negatively correlated, sometimes at statistically significant levels ranging as high as -.68 (Goldman-Eisler, 1961), while verbal quantity and reaction time also tend to be negatively related, though significantly so in only one (Matarazzo, Saslow, & Hare, 1958) of five studies. The longer a person talks the slower his speech rate, though of four studies none reported a significant relationship (for example, Kelly & Steer, 1949).…”
mentioning
confidence: 97%
“…In answering this question, we initially employed Chapple's Interaction Chronograph and the ten speech variables that it generated (Matarazzo et al, 1956). However, a subsequent factor analysis (Matarazzo, Saslow, & Hare, 1958) revealed that many of these ten variables were redundant, and that two variables (speech and silence durations), and possibly a third (a speaker's interruption of his partner or similar "maladjustment" in synchrony), more than adequately recorded what previously had required ten separate measures. We then developed our own successor to the Chapple chronograph, the Interaction Recorder Oohnston, Jansen, Weitman, Hess, Matarazzo, & Saslow, 1961;.…”
Section: Description Of the Scoring Systemmentioning
confidence: 99%
“…We (Matarazzo, Saslow, & Hare, 1958) conducted a factor analysis of twelve of the interview interaction measures recorded by the earlieremployed Chapple Interaction Chronograph. This factor analysis of the data of 60 subjects, as well as a replication study, revealed the presence of four independent factors: two major (speech and silence) and two weaker (initiative and interruption-maladjustment).…”
Section: Dimensionality Considera Nonsmentioning
confidence: 99%
“…The remaining nine measures are second-order or derivative. Measures of two major variables ("speech" and "silence"), which have been shown ( 2 ) to account for about 88 percent of the variance of the twelve measures, cannot be read directly from the Chapple Interaction Chronograph, although they can be derived fairly readily by a scorer. While it is possible, from the printed Interaction Chronograph record, to obtain sums of raw scores, the record does not permit calculation of the variance of any of these variables.…”
Section: Problemmentioning
confidence: 99%